Kekerasan Dan Problem Dialog Antar Agama Di Indonesia - Zuly Qodir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
This articles attempts to describe religion violence. Why religions are raised violence roots? What is problem of the religion dialogue in Indonesia ? How is prospect religious dialogue ? How to construct a mutual dialogue ? This article declares that violence of religions because of sacred text, dogma and the interpretation of text. Absolutely versus relatively, and humanism versus God. Violence of religions departs from ulama, pastor, religious leader, missionaries and religious teacher. Religions ambivalence between peace and violence, because in the religion on text and context are very rigid. The holy war was justified by religious text. Among problems of religious dialogue are collective identity, minority and majority issues, Christianization and Islamization issues, and the conversion of religion. Continued dialogue with cutting crucial issues; collective identity, minority-majority, Christianization and Islamization and conversion.